Hubungan Pengetahuan dengan Praktik Pencegahan Kecelakaaan pada Orang yang Mempunyai Anak Usia Sekolah di SDN Pandeyan Yogyakarta Tahun 2008 - Pangestuti, Travilla Bastian Ajeng (STIKES 'Aisyiyah Yogyakarta, 2008)
Abstract: The purpose of this non experimental research, using correlative design and cross sectional approach, executed toward 57 parents of scool-age childrent prevention practice of parents having school age children studying at Pandeyan elementary School Yogyakarta, in 2008. The result, the research result shows that there is a significant relation between parents’ knowledge about accident prevention and practices of preventing accidents with the value of r (Spearman’s rho) is 0.305, the significant level (r) is 0.021; p< 0.05.